"Szolnok megye a népek országútján" : Szolnok megye története a régészeti leletek tükrében : állandó kiállitás vezetője - Damjanich János Múzeum; Raczky Pál (Szolnok, Damjanich János Múzeum, 1982)
Summaries
Katalog muzejske zbirke
Na uspor. nasl. str.: "Szolnok county, the crossroads of many races" : the history of Szolnok county through archaeologicalfinds : guide to the archaeological collection
Bibliografija iza svakog poglavlja
Keywords: Mađarska - povijest; arheološka nalazišta; arheološki nalazi; muzejske zbirke; arheološka zbirka